MANUALLY OPERATED ROTARY LAWN MOWER - Pamujula hythika madhav; Bhaskar H.B (International Journal of Innovations in Engineering Research and Technology, 2021)
The main objective of the work is to develop the manually operated rotary lawn mower to clean the lawn. Rotary mower has a set of three wheels, one front wheel and two rear wheels. The shaft between the two rear wheels is connected to the compound gear train system. The wheels are rotated in forward motion and bevel gear system convert the forward motion to the vertical motion. The bevel gear system is connected to the blade and the blade is a low lift blade used for low speed. This lawn mower is used to minimize the cost and power requirement for domestic purpose. Since heavy machine cannot be introduced in domestic purpose due to the limited space of lawn